The Effect of A Storage Time Up to 28 Days on The Quality Of Duck Eggs in The Jimbaran Area - I K. A., Setiawan; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of a storage time of up to 28 days on the quality of duck eggs in Jimbaran Region. This research was conducted at the Poultry Laboratory in the Faculty of Animal Husbandry, Udayana University, this study counducted 4 week. The design that be used in this study is a completely randomized design with 5 treatments, 4 replications, each replication consisting of 3 eggs so that the total eggs used are 60. The variables observed were based on external quality which consisted of egg weight and egg shape index. Whereas based on internal quality consisting of eggshell thickness, eggshell weight, Haugh Unit of eggs, of yolk color and pH of eggs. The results showed that external quality, of egg weight and egg index gave no significant differences (P> 0.05). This was also obtained from internal variables, namely eggshell thickness, eggshell weight, egg yolks color obtained similar results no significant different (P>0,05). Whereas on Haugh Unit at 7 days (P7) storage treatment gave significantly different results (P <0.05). Based on the results of the study it can be concluded that the storage of duck eggs for 28 days at 28 ? in Jimbaran did not affect egg weight, egg index, eggshell thickness, eggshell weight, yolk color and pH, while the effect of decreased Haugh Unit of  duck eggs.   Keywords: duck eggs, storage time, eggs quality